2018
DOI: 10.24959/nphj.18.2225
|View full text |Cite
|
Sign up to set email alerts
|

Saponins of the extracts of Galium aparine and Galium verum

Abstract: Aim. To determine the qualitative composition and the quantitative content of saponins in the liquid extracts of the herb of cleavers (Galium aparine L.) and lady's bedstraw (Galium verum L.). Materials and methods. Extracts of the herb of cleavers and lady's bedstraw were obtained by the triple extraction of the raw material with 96 % ethanol when heating with the subsequent concentration of the combined extracts to the ratio of the raw material : the finished product of 1 : 1. Saponins were studied by the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
6
1
2
Order By: Relevance
“…Extensive research on the phytochemical composition of G. aparine showed that cleavers herb contains iridoids: asperulosidic acid and 10-deacetylasperulosidic acid [14], monotropein, asperuloside, acumine and aucubin [15]; alkaloids: protopine, harmine, (±)-vasicinone, (−)-l-hydroxypeganine and (−)-8-hydroxy-2,3-dihydrodesoxypeganine [16]; phenolcarbonic and hydroxycinnamic acids: chlorogenic, caffeic, n-coumaric, ferulic, caftaric and gentisic [17,18]; flavonoids: quercetin, dihydroquercetin, rutin, hyperosid, isoquercetrin, kaempferol, kaempferol-3-O-glucoside (astragalin), epicatechin, neohesperidin, luteolin, luteolin-7-O-diglucoside and apigenin [18][19][20][21]; cholesterol, campesterol, stigmasterol, sitosterol, ∆-[5]-avenasterol, ∆-[7]-stigmasterol and ∆-[7]-avenasterol [21][22][23]. According to our previous studies triterpenoids (oleanolic, ursolic, euscaphic and tormentic acids, betulin and lupeol), sesquiterpenoids, squalene, aromatic compounds and higher alkanes, and their derivatives fatty acids, chlorophylls, and carotenoids were identified in extracts of cleavers herb [24,25].The extract from the herb of G. aparine is one of the ingredients of some galenic remedies and dietary supplement that are recommended as immunomodulatory, anti-inflammatory and for detoxication, as well as for the improvement of the functioning of the lymphatic and blood circulatory systems and a drainage drug, based on the activation of the immune system and normalization of impaired functions.In the ethnopharmacology of many countries, the herb of G. aparine is used for treatment of skin diseases [26][27][28].In the literature several biological activities of G. aparine are reported. Previous studies confirmed antimicrobial, antioxidant and anti-cancer effects of different extracts from this plant material [18,25,29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research on the phytochemical composition of G. aparine showed that cleavers herb contains iridoids: asperulosidic acid and 10-deacetylasperulosidic acid [14], monotropein, asperuloside, acumine and aucubin [15]; alkaloids: protopine, harmine, (±)-vasicinone, (−)-l-hydroxypeganine and (−)-8-hydroxy-2,3-dihydrodesoxypeganine [16]; phenolcarbonic and hydroxycinnamic acids: chlorogenic, caffeic, n-coumaric, ferulic, caftaric and gentisic [17,18]; flavonoids: quercetin, dihydroquercetin, rutin, hyperosid, isoquercetrin, kaempferol, kaempferol-3-O-glucoside (astragalin), epicatechin, neohesperidin, luteolin, luteolin-7-O-diglucoside and apigenin [18][19][20][21]; cholesterol, campesterol, stigmasterol, sitosterol, ∆-[5]-avenasterol, ∆-[7]-stigmasterol and ∆-[7]-avenasterol [21][22][23]. According to our previous studies triterpenoids (oleanolic, ursolic, euscaphic and tormentic acids, betulin and lupeol), sesquiterpenoids, squalene, aromatic compounds and higher alkanes, and their derivatives fatty acids, chlorophylls, and carotenoids were identified in extracts of cleavers herb [24,25].The extract from the herb of G. aparine is one of the ingredients of some galenic remedies and dietary supplement that are recommended as immunomodulatory, anti-inflammatory and for detoxication, as well as for the improvement of the functioning of the lymphatic and blood circulatory systems and a drainage drug, based on the activation of the immune system and normalization of impaired functions.In the ethnopharmacology of many countries, the herb of G. aparine is used for treatment of skin diseases [26][27][28].In the literature several biological activities of G. aparine are reported. Previous studies confirmed antimicrobial, antioxidant and anti-cancer effects of different extracts from this plant material [18,25,29].…”
mentioning
confidence: 99%
“…Extensive research on the phytochemical composition of G. aparine showed that cleavers herb contains iridoids: asperulosidic acid and 10-deacetylasperulosidic acid [14], monotropein, asperuloside, acumine and aucubin [15]; alkaloids: protopine, harmine, (±)-vasicinone, (−)-l-hydroxypeganine and (−)-8-hydroxy-2,3-dihydrodesoxypeganine [16]; phenolcarbonic and hydroxycinnamic acids: chlorogenic, caffeic, n-coumaric, ferulic, caftaric and gentisic [17,18]; flavonoids: quercetin, dihydroquercetin, rutin, hyperosid, isoquercetrin, kaempferol, kaempferol-3-O-glucoside (astragalin), epicatechin, neohesperidin, luteolin, luteolin-7-O-diglucoside and apigenin [18][19][20][21]; cholesterol, campesterol, stigmasterol, sitosterol, ∆-[5]-avenasterol, ∆-[7]-stigmasterol and ∆-[7]-avenasterol [21][22][23]. According to our previous studies triterpenoids (oleanolic, ursolic, euscaphic and tormentic acids, betulin and lupeol), sesquiterpenoids, squalene, aromatic compounds and higher alkanes, and their derivatives fatty acids, chlorophylls, and carotenoids were identified in extracts of cleavers herb [24,25].…”
mentioning
confidence: 99%
“…The identification of the components was carried out by the retention time and the compliance of the UV spectra with the substance standards. The spectra of triterpene saponins have a maximum absorption at (200-210) nm, so detection of this group of compounds was carried out at 205 nm [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Ідентифікацію компонентів проводили за часом утримування і за відповідністю УФ-спектрів досліджуваних речовин речовинам стандартів. Спектри тритерпенових сапонінів мають максимум поглинання за 200-210 нм, тому детектування цієї групи сполук проводили за 205 нм [19,20].…”
Section: матеріали та методиunclassified